2019
DOI: 10.1063/1.5097880
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectricity in YO1.5-HfO2 films around 1 μm in thickness

Abstract: Ferroelectricity has been demonstrated in polycrystalline 7%Y-doped HfO2 (YHO7) films with thicknesses ranging from 10 to 930 nm, which were grown on (111)Pt/TiOx/SiO2/(001)Si substrates by pulsed laser deposition at room temperature and subsequent annealing at 1000 °C. The X-ray diffraction pattern suggested that the major crystal phase consists of orthorhombic/tetragonal phases with a small amount of monoclinic phase even for the 930-nm-thick film despite its thickness. Moreover, the hysteresis loops associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 35 publications
3
67
0
Order By: Relevance
“…Nanoscopic ferroelectricity in hafnia-based thin films has been of significant interest from both fundamental and application points of view 1,2 ever since its discovery. 3 Doped-hafnia films as thin as 1 nm and as thick as 1 lm have exhibited ferroelectric (FE) behavior, 4,5 and this is related to the existence and stabilization of a polar phase. While the orthorhombic (o-) phase (Pca2 1 ) is the least energetic polar phase and is commonly observed through various synthesis procedures, a higher energy rhombohedral phase (R3m, R3) was also shown to be stabilized under specific conditions in epitaxial Hf 0.5 Zr 0.5 O 2 systems (HZO).…”
mentioning
confidence: 99%
“…Nanoscopic ferroelectricity in hafnia-based thin films has been of significant interest from both fundamental and application points of view 1,2 ever since its discovery. 3 Doped-hafnia films as thin as 1 nm and as thick as 1 lm have exhibited ferroelectric (FE) behavior, 4,5 and this is related to the existence and stabilization of a polar phase. While the orthorhombic (o-) phase (Pca2 1 ) is the least energetic polar phase and is commonly observed through various synthesis procedures, a higher energy rhombohedral phase (R3m, R3) was also shown to be stabilized under specific conditions in epitaxial Hf 0.5 Zr 0.5 O 2 systems (HZO).…”
mentioning
confidence: 99%
“…It was proposed that this is the reason why the diminishment of the FE properties with increasing film thickness was only very minor. However, a recent study by Mimura et al utilized pulsed laser deposition at room temperature and a subsequent crystallization anneal at 1000 °C to establish FE films with up to 200 nm large grains of Y:HfO 2 . They concluded that surface energy contributions were negligible and the FE phase is stabilized by the impact of the dopant, which is supported by the high‐temperature XRD.…”
mentioning
confidence: 99%
“…Ferroelectric thin films are of great interest for a wide range of applications such as non‐volatile memory,1 sensors,2 energy storage,3 neuronal networks,4 and future RF devices 5. Doped hafnium oxide combines sizeable spontaneous polarization, remarkable scalability from the micrometer scale6 down to few nanometers,7 and CMOS compatibility. Since the discovery of this prospective material,8 many publications have assessed the formation of the ferroelectric phase in HfO 2 films.…”
mentioning
confidence: 99%
“…
hafnium oxide combines sizeable spontaneous polarization, remarkable scalability from the micro meter scale [6] down to few nano meters, [7] and CMOS compatibility. Since the discovery of this prospective material, [8] many publications have assessed the formation of the ferroelectric phase in HfO 2 films.
…”
mentioning
confidence: 99%
See 1 more Smart Citation